Serum Oxidative Stress Markers and Lipidomic Profile to Detect NASH Patients Responsive to an Antioxidant Treatment: A Pilot Study. (2nd June 2014) - Stiuso, Paola; Scognamiglio, Ilaria; Murolo, Marianna; Ferranti, Pasquale; De Simone, Carmela; Rizzo, Maria Rosaria; Tuccillo, Concetta; Caraglia, Michele; Loguercio, Carmelina; Federico, Alessandro
Abstract : Liver steatosis can evolve to steatohepatitis (NASH) through a series of biochemical steps related to oxidative stress in hepatocytes. Antioxidants, such as silybin, have been proposed as a treatment of patients with nonalcoholic fatty liver disease (NAFLD) and NASH. In this study, we evaluated, in patients with histologically documented NASH, the oxidant/antioxidant status and lipid "fingerprint" in the serum of NASH patients, both in basal conditions and after 12 months of treatment with silybin-based food integrator Realsil (RA). The oxidant/antioxidant status analysis showed the presence of a group of patients with higher basal severity of disease (NAS scores 4.67 ± 2.5) and a second group corresponding to borderline NASH (NAS scores = 3.8 ± 1.5). The chronic treatment with RA changed the NAS score in both groups that reached the statistical significance only in group 2, in which there was also a significant decrease of serum lipid peroxidation. The lipidomic profile showed a lipid composition similar to that of healthy subjects with a restoration of the values of free cholesterol, lysoPC, SM, and PC only in group 2 of patients after treatment with RA. Conclusion. These data suggest that lipidomic and/or oxidative status of serum from patients with NASH could be useful as prognostic markers of response to an antioxidant treatment.